Assessment and Enhancementofthe Manufacturing Productivity through Discrete Event Simulation. Issue 1 (1st January 2022) - Alsaadi, Naif
Abstract: A balanced and resource-efficient assembly line plays a pivotal role in deciding the profit or loss of an industry. In automotive industries, the productivity of the specific materials is highly dependent on several explanatory variables and the processing operations. Moreover, in this 21 st century, simulation is considered a powerful and cost-efficient tool for the designing and analysis of manufacturing operations. Therefore, in this research work, a case-study-based assessment of the assembly line in an automotive component vendor company has been proposed through the study of discrete events. Different processing operations are analyzed in terms of the productivity and effective utilization of available resources. The proposed model is set up by taking actual data using time study techniques from each workstation and process along the production line. All the processes, starting from the arrival of raw materials, forging, to the packing of final products are studied and their data is used to set up a model in software. A detailed statistical distribution of the data urged us to simulate the working area in the virtual environment under the different scenarios to define the bottlenecks. The simulation results have elaborated the realistic sense and meaningful contribution towards the performance enhancement of all the processes involved in the production line. Interestingly, Discrete event simulation has helped us to increase productivity as well as reduce the cost by eradicating the less used resources of the assembly line. Based on the results obtained, it is highly recommended to utilize the proposed methodology in the production system for acquiring better-quality and cost-effective products.